Association between weight-adjusted-waist index and female infertility: a population-based study - Wen, Zujun; Li, Xiang (Frontiers in Endocrinology, 2023)
Obesity is detrimental to infertility. The association between weight-adjustedwaist index (WWI, a recently developed adiposity indicator) and infertility has not previously been confirmed.The data for this study were obtained from the National Health and Nutrition Examination Survey (NHANES) 2013-2018. Each participant's WWI was calculated as their waist circumference in centimeters by the square root of weight in kilograms. Multivariable logistic regression and generalized additive model were utilized to investigate the relationship between WWI with infertility. We used smoothed curve fitting to explore the non-linear relationship. Subgroup analysis and interaction tests were also conducted.A total of 3,526 participants with ages from18 to 45 were enrolled, 364 of whom were infertile. With the higher WWI, infertility was more prevalent (OR = 1.42, 95% CI: 1.22-1.65), and this association was still consistent in subgroups (all P for interaction> 0.05). Smoothed curve fitting showed a positive non-linear relationship between WWI and infertility. Furthermore, we discovered that WWI had a stronger connection with the risk of infertility than other markers of obesity including WC、 body mass index (BMI) and a body shape index (ABSI).Weight-adjusted-waist index levels were positively linked to an increased risk of infertility in American females and showed a stronger association than other markers of obesity. Our research indicated WWI could help identify women with infertility, and managing obesity as determined by WWI may help to reduce the risk of infertility.